Fragmentation of residential units in Baghdad city: Applied research for the municipality of the shaeb - Rabee, Mohammed salih (Al-Adab Journal, 2020)
The phenomenon of fragmentation of the large housing unit into smaller units is strange to Iraqi society and was not familiar with families before, because the small housing unit is a violation of the comfort of the individual in a place where all amenities must be available, and despite the deepening of the housing crisis in Iraq for a long time because of the However, after 2003, weak laws and weak municipal monitoring, people began to fragment their homes for many reasons, including economic, resulting from the low standard of living of more than 36% of the city's households or social reasons after the inflation of households due to high population growth rate. Consequently, the housing unit is no longer sufficient for a family of 10-12 members, forcing the head of the household to split the housing unit in line with the number of his children to gain independence.Personal reasons are another factor related to the standard of living, that is, the owner of the house to divide his house and sell it in the so-called real estate speculation. In addition, governments repudiate the housing needs of the population. Today, we face a real humanitarian catastrophe: housing in small housing units that do not have the minimum human dignityAl-Sha'ab Municipality was chosen as a sample of research as one of the poor municipal units whose inhabitants have not yet realized the process of excessive growth, thus increasing the number of families in them requiring new housing units.